High‐order motor cortex in rats receives somatosensory inputs from the primary motor cortex via cortico‐cortical pathways. (19th October 2016) - Kunori, Nobuo; Takashima, Ichiro
Abstract: The motor cortex of rats contains two forelimb motor areas; the caudal forelimb area (CFA) and the rostral forelimb area (RFA). Although the RFA is thought to correspond to the premotor and/or supplementary motor cortices of primates, which are higher‐order motor areas that receive somatosensory inputs, it is unknown whether the RFA of rats receives somatosensory inputs in the same manner. To investigate this issue, voltage‐sensitive dye (VSD) imaging was used to assess the motor cortex in rats following a brief electrical stimulation of the forelimb. This procedure was followed by intracortical microstimulation (ICMS) mapping to identify the motor representations in the imaged cortex. The combined use of VSD imaging and ICMS revealed that both the CFA and RFA received excitatory synaptic inputs after forelimb stimulation. Further evaluation of the sensory input pathway to the RFA revealed that the forelimb‐evoked RFA response was abolished either by the pharmacological inactivation of the CFA or a cortical transection between the CFA and RFA. These results suggest that forelimb‐related sensory inputs would be transmitted to the RFA from the CFA via the cortico‐cortical pathway. Thus, the present findings imply that sensory information processed in the RFA may be used for the generation of coordinated forelimb movements, which would be similar to the function of the higher‐order motor cortex in primates. Abstract : Voltage‐sensitive dye imaging and intracortical microstimulation experiments revealed that both the primary (M1) and secondary (M2) motor cortex of rats received excitatory synaptic inputs after forelimb stimulation. The forelimb‐evoked M2 response was abolished by pharmacological inactivation of M1 as well as by a cortical transection between M1 and M2, which suggests that M2 receives forelimb sensory information from M1 via the cortico‐cortical pathway.